Speaking Up: A Comprehensive Investigation of EFL Secondary Students' Speaking Skill Problems in Indonesia's Islamic School Context - Rusdin, Rusdin; Purwati, Diana (Elsya : Journal of English Language Studies, 2023)
This study aims to explore the problems encountered by EFL secondary students in learning speaking skills in the context of Islamic schools in Indonesia. The study employed a descriptive qualitative method and used observation, interview, and questionnaire as data collection instruments. The findings revealed that the problems encountered by students in speaking skills can be categorized into four groups: language problems, mental problems, personal problems, and education problems. Language problems included mother tongue interference, poor pronunciation, poor grammar, unnatural spoken English, slow speech, and limited vocabulary. Mental problems included nervousness, shame, low confidence, and lack of ideas. Personal problems consisted of attitude, laziness, environmental effects, and cultural gaps. Finally, education problems included the technique and method of teaching, facilities in teaching-learning, and limited use of media. The results of the study underscore the importance of speaking instruction for EFL learners and the need for teachers and researchers to consider language learners' speaking needs in the context of teaching and learning English. This study contributes to the ongoing discussion on EFL speaking instruction and provides implications for teachers and researchers in designing effective language teaching programs.